2011
DOI: 10.1115/1.4003065
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Structure of the Tip Leakage Vortex Within the Rotor of an Axial Waterjet Pump

Abstract: The complex flow field in the tip region of a turbomachine rotor, including the tip leakage flow and tip leakage vortex (TLV), has been studied for decades. Yet many associated phenomena are still not understood. This paper provides detailed data on the instantaneous and phase-averaged inner structures of the tip flow and evolution of the TLV. Observations are based on series of high resolution planar particle image velocimetry measurements performed in a transparent waterjet pump fitted into an optical refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(45 citation statements)
references
References 35 publications
4
41
0
Order By: Relevance
“…Pressure fluctuation coefficients of points S5-S9 decrease gradually from inlet to outlet of the guide vane at all conditions, which illustrates that rotor-stator influence is weak; meanwhile, pressure fluctuation variation at corresponding points at the shroud region is small at different clearance conditions, which illustrates that clearance variation has less effect on fluctuation at the shroud region of the guide vane. Through MATLAB post processing, the distribution of in the guide vane passage was obtained according to Equation (10). Figure 15 shows the distribution of on the central hub-toshroud surface of the guide vane at the design condition.…”
Section: Influence Of Tip Clearance On Pressure Fluctuation In the Gumentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure fluctuation coefficients of points S5-S9 decrease gradually from inlet to outlet of the guide vane at all conditions, which illustrates that rotor-stator influence is weak; meanwhile, pressure fluctuation variation at corresponding points at the shroud region is small at different clearance conditions, which illustrates that clearance variation has less effect on fluctuation at the shroud region of the guide vane. Through MATLAB post processing, the distribution of in the guide vane passage was obtained according to Equation (10). Figure 15 shows the distribution of on the central hub-toshroud surface of the guide vane at the design condition.…”
Section: Influence Of Tip Clearance On Pressure Fluctuation In the Gumentioning
confidence: 99%
“…In recent years, research has been conducted on the influence of tip clearance on performance [5,6], pressure fluctuation [7][8][9] and internal flow of pumps [10,11], but the subjects have mainly been centrifugal pumps and axial pumps. For mixed-flow pumps, related research has mainly concentrated on the influence of clearance size on performance parameters and tip-leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [7][8][9][10] performed a series of experiments by using particle image velocimetry measurements to study the flow structures in the tip region of a water-jet pump rotor, including the tip clearance flow, tip leakage vortex and cavitation flow; they found that the tip leakage vortex started to form near the suction-side edge of a blade tip and appeared as a swirling jet, migrating to the middle of the blade passage. The backward leakage flow penetrated into the passage and created a shear layer in the interface with the main flow.…”
Section: Introductionmentioning
confidence: 99%
“…Asim et al [14] applied the Q-criterion to illustrate that a secondary flow generated near the volute tongue, with an impact on the pump head. Miorini et al [15] and Zhou et al…”
mentioning
confidence: 99%
“…Asim et al [14] applied the Q-criterion to illustrate that a secondary flow generated near the volute tongue, with an impact on the pump head. Miorini et al [15] and Zhou et al[16] adopted a vorticity study to investigate tip leakage flow and rotating stall, respectively, to describe the development of these unsteady flow phenomena and to prove their effects on pump performance. These methods are able to make apparent specific flow structures inside the centrifugal pump, and could assist the design and optimization of centrifugal pumps [17][18][19].The quantity of energy loss related to these particular flow structures, needs to be investigated in details, at different operating conditions.…”
mentioning
confidence: 99%